2018
DOI: 10.1186/s12958-018-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changes in the number of uterine natural killer cells are specific to the eutopic but not to the ectopic endometrium in women and in a baboon model of endometriosis

Abstract: BackgroundEndometriosis is a common condition associated with growth of endometrial-like tissue beyond the uterine cavity. Previous reports have suggested a role for uNK cells in the pathogenesis of endometriosis postulating that survival and accumulation of menstrual endometrial tissue in the peritoneal cavity may relate to a reduction in the cytotoxic activity of peripheral blood NK cells. We aimed to assess the differences in percentage of uNK cells and their phenotypical characterization in eutopic and ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…The upregulation of KIR2DS1 expression in peritoneal fluid has been detected in women with endometriosis 72 . Recently, bioinformatic analysis showed that KIR2DS2 expression is upregulated in the secretory phase of endometrium in women with endometriosis relative to control women 73 . Thus, the regulation of NK cell activity is a complex process and can affect the pathogenesis of endometriosis 74 .…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of KIR2DS1 expression in peritoneal fluid has been detected in women with endometriosis 72 . Recently, bioinformatic analysis showed that KIR2DS2 expression is upregulated in the secretory phase of endometrium in women with endometriosis relative to control women 73 . Thus, the regulation of NK cell activity is a complex process and can affect the pathogenesis of endometriosis 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Other have found a periovulatory increase (16). The percentage of endometrial NK cells in the stromal compartment rose up to 7.35% in the late secretory phase (17). Reports are conflicting about the number and activity of these cells.…”
Section: Nature Killer Cellsmentioning
confidence: 99%
“…Furthermore, there were no changes in CD56 + cells. On the other hand, there are reports showing that the numbers of CD56 + or CD16 + cells in endometriotic tissues are lower than in eutopic endometrium from healthy women [90,97] and that NK cells from endometriotic lesions do not show typical changes characteristic to uNK cells in the eutopic endometrium [98].…”
Section: Frequency Of Nk Cell In Patients With Endometriosismentioning
confidence: 99%